An introduction to Western medical acupuncture - White, Adrian; Cummings, T. M. (Thomas Michael), 1963-; Filshie, Jacqueline; ScienceDirect eBooks (Edinburgh : Churchill Livingstone/Elsevier, 2008)
This book is a clear and practical introductory guide to the practice of medical acupuncture. It describes the Western medical approach to the use of acupuncture as a therapy following orthodox diagnosis. The text covers issues of safety, different approaches to acupuncture, basic point information, clinical issues and the application of acupuncture in clinical conditions, especially in the treatment of pain. A practical guide to the principles and clinical practice of medical acupunctureA clear guide to the neurophysiological principles which underlie medical approaches to acupunctureA basic explanation of the different styles of medical acupuncture treatmentAllows the reader to accrue the practical knowledge necessary before beginning to work with medical acupuncture.
Glossary -- 1. Introduction -- Section I Principles -- 2. An overview of Western medical acupuncture -- 3. Neurological mechanisms I: local effects -- 4. Neurological mechanisms II: segmental analgesia -- 5. Neurological mechanisms III: extrasegmental analgesia -- 6. Neurological mechanisms IV: central regulatory effects -- 7. Myofascial trigger points -- 8. Traditional Chinese acupuncture reinterpreted -- Section II: The evidence -- 9. Clinical research into the effectiveness of acupuncture -- 10. Evidence on the safety of acupuncture -- Section III: Practical aspects -- 11. Preparation for treatment -- 12. Effective needling techniques -- 13. Safe needling -- 14. Other acupuncture techniques -- Section IV: Treatment manual -- 15. Treatment guidelines -- 16. Reference charts: points and innervation -- References -- Index.
Includes bibliographical references and index.
Print version record.
Elsevier
Keywords: Acupuncture; MEDICAL -- Pharmacology; Acupuncture; Acupuncture; Electronic books